2, 3′, 4, 4′, 5‐Pentachlorobiphenyl attenuated fast‐twitch fibers and fiber size of skeletal muscle via disturbing thyroid hormone signaling and mitochondrial dynamics. Issue 10 (21st April 2022) - Zhu, Xiaoxia; Zou, Yuxin; Qi, Xinyu; Sheng, Yunlu; Lv, Shan; Yu, Jing; Wang, Xiaodong; Ding, Guoxian; Duan, Yu
Abstract: Polychlorinated biphenyls (PCBs) affect multiple organs, and some of the effects are mediated by interfering with thyroid hormone (TH) signaling that regulates physiological processes in mammals. It remains unclear how PCBs affect skeletal muscle (SM). In our study, wistar rats were injected 2, 3′, 4, 4′, 5‐pentachlorobiphenyl (PCB118) intraperitoneally at 0, 10, 100, and 1000 μg/kg/day for 13 weeks, and C2C12 myoblasts were treated PCB118 (0, 0.25, 25, and 50 nM) for 24 h or 48 h. We found that myocyte cross‐sectional area (MCSA) was reduced, MyHC IIa and MyHC IIb mRNA levels significantly decreased, and muscle strength was weakened in PCB118‐exposed rats. TH receptor α (TRα) and iodothyronine deiodinase type 2 (DIO2) were upregulated after PCB118 exposure both in vivo and in vitro. Transmission electron microscopy showed significant mitochondrial abnormalities in PCB118‐treated rats, and the expression of mitochondrial regulators such as PTEN‐induced kinase 1 (PINK1) and GTPase dynamin‐related protein 1 (DRP1) were altered after PCB118 exposure. These results suggest that PCB118 could weaken muscle strength and attenuate fast‐twitch fibers and fiber size of SM in rats. TH signaling, mitochondrial dynamics and mitophagy were also disturbed by PCB118, which may contribute to the alternations of SM structure and function. Abstract : 2, 3′, 4, 4′, 5‐Pentachlorobiphenyl could weaken muscle strength and attenuate fast‐twitch fibers and fiber size of SM, which are the main characteristics of sarcopenia. TH signaling, mitochondrial morphology, and PINK1 and DRP1 expressions were also disturbed by PCB118, which may contribute to the alternations of SM structure and function.